Controversies Surrounding the Constitutional Court’s Role as a Positive Legislator - Basuki Kurniawan; Sareef Tehtae; Jati Nugroho; Anis Ibrahim; Asir Asir; Henny Purwanti (Fenomena, 2025)
The Constitutional Court’s growing involvement in regulatory matters has sparked intense debate, particularly following Decision No. 90/PUU-XXI/2023 on the age requirement for presidential and vice-presidential candidates. Issued near the candidate registration deadline, this ruling raised concerns about the Court's shift from a negative to a positive legislator. Previous studies have not adequately examined this transformation through the lens of classical justice theory, leaving a critical gap in constitutional discourse. This study aims to (1) assess whether the decision constitutes a positive legislator act, (2) evaluate it through classical justice theory, and (3) compare it with similar rulings. Using normative legal research, it adopts statutory, case, and conceptual approaches, with legal reasoning conducted through analogical and deductive interpretations of judicial precedents, constitutional norms, and principles of justice. The analysis reveals that the Court has increasingly assumed regulatory functions, with Decision No. 90 exemplifying this trend. However, it does not align with Platonic ideals of justice, lacking both moral and procedural fairness. The study concludes that the Court's expanded role poses constitutional risks and fuels ongoing debates on judicial activism versus legislative supremacy, while offering a fresh perspective through the application of classical justice theory. Meningkatnya keterlibatan Mahkamah Konstitusi dalam ranah regulasi telah memicu perdebatan yang intens, khususnya setelah Putusan No. 90/PUU-XXI/2023 terkait syarat usia calon presiden dan wakil presiden. Putusan ini dikeluarkan menjelang tenggat waktu pendaftaran calon, sehingga menimbulkan kekhawatiran mengenai pergeseran peran Mahkamah dari legislator negatif menjadi legislator positif. Studi-studi sebelumnya belum secara memadai mengeksplorasi transformasi ini melalui lensa teori keadilan klasik, sehingga menyisakan kekosongan penting dalam diskursus ketatanegaraan. Penelitian ini bertujuan untuk: (1) menilai apakah putusan tersebut merupakan tindakan legislator positif, (2) mengevaluasinya menggunakan teori keadilan klasik, dan (3) membandingkannya dengan putusan-putusan serupa. Dengan menggunakan metode penelitian hukum normatif, studi ini mengandalkan pendekatan perundang-undangan, kasus, dan konseptual, serta penalaran hukum melalui interpretasi analogis dan deduktif terhadap preseden yudisial, norma-norma konstitusional, dan prinsip-prinsip keadilan. Analisis menunjukkan bahwa Mahkamah semakin mengambil peran regulatif, dan Putusan No. 90 mencerminkan tren tersebut. Namun, putusan ini tidak sejalan dengan cita keadilan menurut Plato karena tidak mencerminkan keadilan moral maupun prosedural. Penelitian ini menyimpulkan bahwa perluasan peran Mahkamah menimbulkan risiko konstitusional dan turut memperkuat perdebatan mengenai aktivisme yudisial versus supremasi legislatif, sembari menawarkan perspektif baru melalui penerapan teori keadilan klasik.